2010
DOI: 10.1172/jci41902
|View full text |Cite
|
Sign up to set email alerts
|

Heterosubtypic neutralizing antibodies are produced by individuals immunized with a seasonal influenza vaccine

Abstract: The target of neutralizing antibodies that protect against influenza virus infection is the viral protein HA. Genetic and antigenic variation in HA has been used to classify influenza viruses into subtypes (H1-H16). The neutralizing antibody response to influenza virus is thought to be specific for a few antigenically related isolates within a given subtype. However, while heterosubtypic antibodies capable of neutralizing multiple influenza virus subtypes have been recently isolated from phage display librarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
435
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(463 citation statements)
references
References 36 publications
24
435
0
2
Order By: Relevance
“…These findings corroborate previous findings made by biochemical analysis of a limited number of samples [4,8]. We have found that vaccination not only enhanced antibody responses to subtypes that are currently circulating, and are therefore included in the vaccine, but also augmented binding and neutralizing antibody titers to Reference age: 0-40 years.…”
Section: Discussionsupporting
confidence: 91%
“…These findings corroborate previous findings made by biochemical analysis of a limited number of samples [4,8]. We have found that vaccination not only enhanced antibody responses to subtypes that are currently circulating, and are therefore included in the vaccine, but also augmented binding and neutralizing antibody titers to Reference age: 0-40 years.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, the highest induction of ADCC in response to HA1 or the HA trimer was detected in the pre-pandemic samples (#3 and #51, Fig. 5 Several studies have shown pre-existing immunity against A(H1N1)2009 in adults (Corti et al, 2010(Corti et al, , 2011Ekiert et al, 2009;Throsby et al, 2008), whereas little or no preexisting cross-reactive antibodies were detected in a group of 124 children aged 6 months to 9 years (Hancock et al, 2009) the HA2 domain, which is not presented in our array (Greenbaum et al, 2009;Li et al, 2012).…”
Section: Adcc Induction Pre-and Post-a(h1n1)2009 Infectionmentioning
confidence: 73%
“…Persons born before the 1940s were most protected against the A (H1N1)2009, which has been related to the similarity between the HA1 of the 1918 and 2009 pandemic strains Xu et al, 2010); however, some protection was also observed in younger adults. Cross-neutralizing antibodies have been implicated in this immune protection, possibly resulting from the boosting of antibodies that had developed against previous seasonal strains ( Corti et al, 2010Corti et al, , 2011Ekiert et al, 2009;Li et al, 2012;Throsby et al, 2008;Wrammert et al, 2011). However, cross-reactive antibodies were hardly detected among children aged 6 months to 9 years (Hancock et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These Abs were shown to have neutralizing activity against multiple influenza subtypes and were identified using a number of systems including phage display (2-4) and immortalization of memory B cells (5). We then demonstrated that these stem-reactive Abs were readily detected in patients infected with the pandemic H1N1 2009 influenza (referred to as pH1N1 2009 from here on) (7).…”
mentioning
confidence: 93%